Implementing Responsible Research and Innovation Organisational and National Conditions - Wittrock, Christian; Forsberg, Ellen-Marie; Pols, Auke; Macnaghten, Philip; Ludwig, David (SpringerBriefs in Ethics,, 2021)
This open access book offers a unique and practically oriented study of organisational and national conditions for implementing Responsible Research Innovation (RRI) policies and practices. It gives the reader a thorough understanding of the different aspects of RRI, and of barriers and drivers of implementation of RRI related policies. It shows how different organisational and national contexts provide unique challenges and opportunities for bringing RRI into practice. The book provides concrete examples and offers the reader both a theory-based understanding of the topic, as well as guidance for action. The target audience encompasses, in addition to RRI students and scholars in particular, all students and scholars in the field of Science and Technology Studies (STS). The book is also of interest to students and scholars in the fields of research ethics, philosophy of science, organisational governance in the research system and organisational theory more generally. Finally, thebook is of use to practitioners in research conducting and funding organisations working to implement RRI. .